2016
DOI: 10.17569/tojqi.21319
|View full text |Cite
|
Sign up to set email alerts
|

Infusing Global Perspectives in Social Studies Education in Turkey: Pre-service Social Studies Teachers

Abstract: The purpose of this study was to explore how pre-service social studies teachers understood global perspectives within social studies education and how they interpreted social studies teacher education program in terms of providing global perspectives. Phenomenological design was employed in order to gather the data. The data obtained as a result of two semistructured interviews with 11 pre-service social studies teachers and participants' journals were analyzed by using NVivo 10 package program. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…On the other hand, a significant group of participants argued that globalization is related to concepts such as imperialism and hegemony. A similar tendency has been noted in previous studies (Gaudelli, 2003;Myers, 2006;Günel & Pehlivan, 2016). Recent studies have stated that there has been a reaction against globalization for different reasons (Frieden, Anadolu University Journal of Education Faculty (AUJEF), 7(1), 84-110 Walter, 2021).…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 84%
See 2 more Smart Citations
“…On the other hand, a significant group of participants argued that globalization is related to concepts such as imperialism and hegemony. A similar tendency has been noted in previous studies (Gaudelli, 2003;Myers, 2006;Günel & Pehlivan, 2016). Recent studies have stated that there has been a reaction against globalization for different reasons (Frieden, Anadolu University Journal of Education Faculty (AUJEF), 7(1), 84-110 Walter, 2021).…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 84%
“…Integration of globalization into teacher education is a relatively recent development. Although a course related to globalization did not directly take place in the teacher education undergraduate curriculum until 2018, studies examining pre-service teachers' global education knowledge, skills, and values (Kaymakçı, 2012;Günel & Pehlivan, 2016) started roughly after the 2010s. Kaymakçı (2012) revealed that the teacher education undergraduate curriculum, which began in 2006, includes courses related to global education but reflects the themes of global education in a limited way.…”
Section: Turkish Social Studies Context and Global Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at the contents of this study, global awareness, training and implementation for student teacher candidates and teachers ' perceptions of and attitudes studies as an example ; Özkan, (2006), Kan, (2009), Öztürk, (2014), Öztürk andGünel, (2016), Körükçü, (2015), Bozkurt and Yaşar (2016) can be shown by studies. Examples include works by Açıkalın, (2010Açıkalın, ( ), Çolak, (2015, Öcal and Yakar, (2015) and Günel, (2016). In addition, there are a small number of applied studies conducted by Egüz, (2017) and Başarır, (2018) on the teaching of themes within the scope of global awareness education.…”
Section: Results and Suggestionmentioning
confidence: 99%
“…In conclusion, the social studies textbooks in Turkey demonstrate both strengths and limitations in their approach to conceptualizing and teaching global citizenship. Research indicated that social studies textbooks in Turkey (Acikalin, 2010;Arar et al, 2016;Ersoy, 2013;Günel & Pehlivan, 2015;Günel, 2016;Kilinc & Tarman, 2018) as well as in numerous other countries (Evans, 2003;Philippou, 2009;Su, 2007) do not adequately address the concept of global citizenship. The incorporation of global citizenship education into educational materials and curricula is limited without sufficient emphasis on social justice, highlighting a widespread gap in promoting a broader understanding of global issues, intercultural competence, and fostering a sense of responsibility towards the global community.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%